Antiplasmodial activity of Anchomanes difformis aqueous leaf extract on Plasmodium berghei infected mice - Bensandy Odeghe; Elias Adikwu; Frances John (Shiraz University of Medical Sciences, 2020)
Challenges including treatment failure, cost, resistance, and adverse effects associated with antimalarial drugs have increased the use of medical plants as alternative treatment. Anchomanes difformis (A. difformis) is a multipurpose plant used traditionally for the treatment of a variety of ailments including malaria, but with a paucity of scientific evidence. This study assessed the antiplasmodial activity of A. difformis aqueous leaf extract (AEA) in Plasmodium berghei (P. berghei) infected mice. AEA (100, 200 and 400 mg/kg) was orally administered to P. berghei infected mice in the curative, suppressive and prophylactic groups. The untreated parasitized control (UPC) and the positive control were administered orally with normal saline (0.2mL) and chloroquine (CQ) (10mg/kg). After treatment, blood samples were analyzed for parasitamia level, hematological parameters and liver samples were evaluated for histology. Curative, suppressive and prophylactic studies showed that administered AEA decreased parasitamia levels and increased survival time in a dose-dependent fashion with significance at 200 mg/kg (p